2020
DOI: 10.1111/ene.14643
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of uric acid change in acute ischemic stroke patients with reperfusion therapy

Abstract: Background Uric acid (UA) is an important endogenous free radical scavenger that has been found to have a neuroprotective effect. However, there is uncertainty about the relationship between UA change and outcome in acute ischemic stroke (AIS) patients with reperfusion therapy. Methods We consecutively enrolled AIS patients with reperfusion therapy. UA was measured upon admission and during hospitalization. The change in UA levels (ΔUA) was determined by calculating the difference between admission UA and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Contrary to the previously mentioned relationship between higher uric acid levels and poor outcomes, Tang et al found that lower uric acid levels are associated with poor outcomes [ 15 ]. However, higher uric acid levels have been associated with better stroke outcomes in some studies, and in patients with thrombolysis [ 5 , 16 , 17 , 18 , 19 ]. Furthermore, several studies have reported a U-shaped relationship between uric acid and poor stroke outcomes (including mortality) [ 20 , 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrary to the previously mentioned relationship between higher uric acid levels and poor outcomes, Tang et al found that lower uric acid levels are associated with poor outcomes [ 15 ]. However, higher uric acid levels have been associated with better stroke outcomes in some studies, and in patients with thrombolysis [ 5 , 16 , 17 , 18 , 19 ]. Furthermore, several studies have reported a U-shaped relationship between uric acid and poor stroke outcomes (including mortality) [ 20 , 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Uric acid has the useful ability to clear out peroxynitrite, nitric oxide, and hydroxyl radicals. It can therefore protect nerves from oxidative damage during an acute stroke and prevent worse outcomes [ 14 , 18 , 19 ]. However, elevated uric acid was also reported to promote atherosclerotic progression by increasing the production of free radicals and facilitating low-density lipoprotein cholesterol oxidation [ 35 ]; to increase the level of inflammatory cytokines; to increase platelet aggregation and thrombus formation [ 36 ]; and to be associated with carotid intima-media thickness [ 37 ], proximal extracranial artery stenosis [ 38 ], and intracranial arterial stenosis [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7–9 Several observational human studies demonstrated that increased serum UA levels were associated with better clinical outcome after AIS. 10–12 A randomized-controlled trial of intravenous UA administered during alteplase treatment for AIS also revealed that UA therapy had an excellent safety profile and ability to prevent early ischemic deterioration among thrombolysed patients. 13 …”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Several observational human studies demonstrated that increased serum UA levels were associated with better clinical outcome after AIS. [10][11][12] A randomized-controlled trial of intravenous UA administered during alteplase treatment for AIS also revealed that UA therapy had an excellent safety profile and ability to prevent early ischemic deterioration among thrombolysed patients. 13 However, conflicting data have been reported regarding whether increased levels of serum UA are significantly associated with favorable outcomes in patients after ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%